Religious Values Integration in STEM-R Based Science Learning: Insights From Jambi Teachers - Mhd. Abror Muzakkir Muda; Sri Purwaningsih; Nazarudin Nazarudin; Musli Musli (Unversitas Muhammadiyah Mataram, 2026)
The integration of religious values in STEM education remains underexplored, particularly within the context of Islamic-based schools in Indonesia. Understanding how science teachers perceive and implement such integration is crucial for developing culturally responsive pedagogy. This study aims to explore the perceptions, strategies, and challenges faced by science teachers in implementing STEM-R (Science, Technology, Engineering, Mathematics–Religious) in their classrooms. Using a qualitative descriptive method, data were collected through in-depth interviews, classroom observations, and document analysis involving selected science teachers from Islamic-based senior high schools. Visual clustering and thematic analysis were employed to interpret data. The study focused on identifying emotional responses, instructional strategies, reflective practices, and perceived student outcomes related to the STEM-R approach. Findings indicate that teachers perceive STEM-R positively, describing it as spiritually meaningful and pedagogically enriching. The study concludes that STEM-R facilitates holistic education by integrating scientific understanding with ethical and spiritual development. This research contributes to the field by offering empirical insight into STEM-R implementation and proposing a practical model for faith-integrated STEM pedagogy in religious education contexts.